Direklo-Mehdikhan Alkaline Basalt District, an Indication of a Quaternary Continental Within Plate Extensional Mechanism - Fatemeh Narimani; MohammadAli Mackizadeh; Mortaza Sharifi (پترولوژی)
IntroductionThe Direklo-Mehdikhan volcanic district is the largest volcanic region within the Qorveh-Bijar Quaternary volcanic belt, located near Qorveh in Kurdistan province, Iran. The Qorveh-Bijar Quaternary basic volcanic belt lies between the provinces of West Azerbaijan and Kurdistan, within the Sanandaj-Sirjan zone as a segment of the Alpine-Himalayan Orogeny with a Gondwana-affinity basement. The Orogeny is strongly influenced by the Middle-Late Tertiary post-orogenic development that followed the continental collision between the Arabian and Eurasian plates. Following the collision, the SSZ continental lithosphere was thickened (Agard et al., 2005), leading to a lithospheric thickness of ~150–170 km (Priestley and McKenzie, 2006). In this district, the deposits of pyroclastic origins and scoria, which erupted from a thick lithosphere, are covered by alkaline basic lava flows (Neill et al., 2015).The primary objective of the present study is to provide evidences for the subduction of the Neotethys oceanic plate beneath the Eurasian margin and the collision of the Arabian plate. Therefore, this study focuses on the Direklo-Mehdikhan volcanic district.Petrographic observations, along with whole-rock geochemstry and clinopyroxene mineral chemistry, were carried out to enhance our understanding of the magmatic activity of the Direklo-Mehdikhan volcanic district.Research MethodsThe study started by fieldwork, petrographic analysis, and geochemical investigations. Field observations were conducted on the lava flow situated between the villages of Direklo and Mehdikhan. Samples were collected from various locations within the lava flow, and thin sections were prepared for petrographic examination. Additionally, geochemical data on pyroxene crystals and whole-rock samples were analyzed to explore the origin and the evolution of the lava flow body. All EMPA and whole-rock analyses were performed at the Central Laboratory of Moscow State University in Russia and the Australian Lab West, respectively.Results and DiscussionThe main mineral components which are defined by aphanitic to porphyritic texture, are phenocrysts mainly consist of olivine and pyroxene. The matrix includes plagioclase, opaque minerals, glass, and similar microcrystalline mineral phases. In some samples, xenoliths and quartz xenocrysts is observed. These fragments likely detached from adjacent rocks and were incorporated during magma ascending the crust. The studied samples primarily exhibit a porphyritic texture, with additional secondary textures observable in some samples, such as glomeroporphyritic, sieve, vesicular, vitrophyric, amygdaloidal, hyalomicrolitic, and microlithic porphyritic. The formation of porphyritic texture formed during a crystallization stage deep within the Earth (where phenocrysts crystallize), followed by further crystallization at or near the Earth's surface, resulting in the development of finer crystals. The presence of a glassy background and the microlithic texture is largely due to insufficient time for the remaining magma to crystallize at shallow depths or close to the surface (Shea, 2017).EPMA results of clinopyroxene indicate that the clinopyroxenes are classified within the iron-magnesium-calcium pyroxenes quadrilateral and are identified as diopside type. The Mg number (Mg#) for these minerals ranges from 0.82 to 0.92 (Figures 5A and 5B). The chemical composition of clinopyroxene demonstrate the alkaline magmatic series, as well as the extensional and intraplate tectonic environments. The crystallization process is believed to have occurred under conditions of high oxygen fugacity (Figures 5C and 5D). The calculated temperature and pressure conditions for the crystallization of clinopyroxenes indicate a pressure range of 6 to 10 kbar and a temperature range of 1160 to 1250 °C (Figure 6). The variation in crystallization pressure is attributed to existence of multiple magma chambers and the clinopyroxene crystallization during the rapid ascent of magma (Özdemir et al., 2020).Based on geochemical discrimination diagrams, the samples plot in the alkaline series and low-SiO2 basalt (Figure 7-A). Normalized rare earth elements (REEs) diagrams, along with various elemental ratios such as Nb/Pb, La/Sm, Nb/U, and La/Yb, reveal a significant enrichment of light rare earth elements compared to heavy elements. This suggests the involvement of an enriched mantle, characterized by the presence of garnet in the source and a low degree of partial melting. So, the magma originated from a garnet lherzolite source during a partial melting process with a melting percentage of less than 5% and showed some clues of crustal contamination (Figures 14 and 15).ConclusionsField studies, petrographic, and geochemical analysis of the Direklo-Mehdikhan low-SiO2 alkaline basalt reveals valuable insights into the subduction of the Neotethys Oceanic crust and post-collisional mantle-derived mafic magmatism within intracontinental extensional settings. Normalized elemental diagrams, in comparison to primitive mantle compositions, reveals an enrichment in large-ion lithophile elements (LILE) and light rare earth elements (LREE) relative to high field strength elements (HFSE). Negative anomalies are observed in niobium (Nb) and titanium (Ti). Petrographic evidence and geochemical data indicate that local extensional and depressurization activities triggered low-grade partial melting (less than 5%). The parent magma derived from enriched garnet lherzolite at the pressure varying from 6 to 10 kbar and a temperature ranging from 1160 to 1250 °C. This process engaged in magma ascending rapidly to surface with minimal contamination by crust.